2017
DOI: 10.1093/biolre/iox175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex differences in zebrafish (Danio rerio) brains during early sexual differentiation and masculinization using 17α-methyltestoterone†

Abstract: Sexual behavior in teleost fish is highly plastic. It can be attributed to the relatively few sex differences found in adult brain transcriptomes. Environmental and hormonal factors can influence sex-specific behavior. Androgen treatment stimulates behavioral masculinization. Sex dimorphic gene expression in developing teleost brains and the molecular basis for androgen-induced behavioral masculinization are poorly understood. In this study, juvenile zebrafish (Danio rerio) were treated with 100 ng/L of 17 alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 170 publications
2
19
0
Order By: Relevance
“…In this study, egr1 which activates the expression of TGFβ and shisa6 which inhibites the canonical Wnt signaling pathway in mammalians (Tokue et al, ) were identified as DEMs. Consistent with the present result, egr1 was also identified as a female‐biased gene in the zebrafish brain on 40 days postfertilization (Lee et al, ). These results indicate that the TGF‐β and Wnt pathways might also be involved in brain sex differentiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, egr1 which activates the expression of TGFβ and shisa6 which inhibites the canonical Wnt signaling pathway in mammalians (Tokue et al, ) were identified as DEMs. Consistent with the present result, egr1 was also identified as a female‐biased gene in the zebrafish brain on 40 days postfertilization (Lee et al, ). These results indicate that the TGF‐β and Wnt pathways might also be involved in brain sex differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, both at 3 and 8 cm TL, the circadian rhythm core genes were differentially expressed and pathways of circadian rhythm and circadian entrainment were enriched in female brains versus male brains. In juvenile zebrafish brain, genes involved in circadian rhythm regulation were differentially expressed, among which npas2 and cry2 were sexually dimorphic expressed in brain on 40 days postfertilization and per1 was sexually dimorphic expressed in brain on 60 days posthatching (Lee, Horsfield, Black, Rutherford, & Gemmell, ). Consistent with these results, npas2 , cry2 , and per1 were also identified as DEGs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Male sex determination begins with the disappearance of oocytes and the decomposition of the ovarian cavity caused by apoptosis (Uchida, Yamashita, Kitano, & Iguchi, ). Several genes, such as brain aromatase ( cyp19a1b ), prostaglandin 3a synthase ( ptges3a ), and prostaglandin reductase 1 ( ptgr1 ) genes, are responsible for fish hormonal regulation and display sexually dimorphic CNS expression patterns (Lee, Horsfield, Black, Rutherford, & Gemmell, ). The Cyp19 gene product enzymatically converts testosterone into 17 beta‐estradiol, and its inhibition leads to male‐to‐female sex reversal (von Hofsten & Olsson, ).…”
Section: The Role Of Sex Differences In Zebrafish Cns Modelsmentioning
confidence: 99%
“…While androgen treatment stimulates behavioral masculinization, it can be reversed by estrogens (von Hofsten & Olsson, ). Androgen treatment upregulates hydroxysteroid 11‐beta dehydrogenase 2 ( hsd11b2 ), deiodinase iodothyronine type II ( dio2 ), gonadotropin‐releasing hormones 2 and 3 ( gnrh2, gnrh3 ) genes, modulating synthesis of 11‐ketotestosterone, triiodothyronine, and GnRHs in zebrafish brain (Lee et al, ). Furthermore, 42 zebrafish brain genes are differentially expressed between the sexes, including 18 genes over‐expressed in males and 24 genes in females (Santos, Kille, Workman, Paull, & Tyler, ).…”
Section: The Role Of Sex Differences In Zebrafish Cns Modelsmentioning
confidence: 99%
“…Gender identity and gender-specific behaviour, however, result from hormonal influences on the sexual differentiation of the brain (Cooke et al, 1998). Genetically male or female individuals can show atypical gender identity if sexual differentiation of the brain is counter to sex chromosome identity; for example, the masculinizing effects of androgens on the fetal brain strongly influence the development of male-specific behaviour (Collaer and Hines, 1995;Lee et al, 2017). Moreover, in many species, all aspects of sex determination are under environmental regulation (Janzen and Phillips, 2006;Kato et al, 2011;Crews et al, 1994).…”
Section: Introductionmentioning
confidence: 99%